Who Assesses the Assessors? Sustainability and Assessment in Art and Design Education. (October 2016) - Robins, Claire
Abstract: This article draws on recent research from the Pre‐Degree Summative Assessment in Art Design and Media Study, conducted at UCL Institute of Education, which found that pre‐degree art and design qualifications at levels 3 and 4 vary greatly in their appropriateness as a preparation for degree level study in art subjects. Central to the article are findings concerning external assessment processes and assessor selection and training. The research was commissioned by the awarding body of University of the Arts London in response to the then imminent Department for Education (DFE) directives for additional external assessment in all level 3 and 4 vocational pre‐degree programmes. Our research revealed the negative consequences of assessment becoming a bureaucratic process of measuring what is most easily measurable. In such instances it can become a task that is devoid of 'expert' knowledge and opinion. As the research demonstrates, the consequences for art education are serious. The title is appropriated from Bourdieu's1993 sociological examination 'But who created the "creators"?' which casts a critical eye on the broader social landscape in which art and artists are produced and imbricated into the wider cultural order. To ask, who assesses the assessors? Is, of course, to ask a different kind of question, but never‐the‐less it is one which deserves to be opened out to scrutiny beyond the specificity of individual qualifications. This article's contribution argues for a more sustainable and radically transparent assessment regime in which professional expertise can be shared across the UK's secondary, further and higher education continuum.